Recent advances in the genetic investigation of osteoarthritis. - Peach, C; Carr, A; Loughlin, J (2005)
Osteoarthritis (OA) demonstrates considerable clinical heterogeneity, generating heated debate over whether OA is a single disease or a complex mix of disparate diseases and concerning which tissues are principally involved in disease initiation and progression. Epidemiological studies have demonstrated a major genetic component to OA risk. However, these studies have also revealed differences in risk between males and females and for disease at different skeletal sites. This observation has resulted in the concept of genes for specific sites rather than a generalised OA phenotype. Recent breakthroughs have shed considerable light on the nature of OA genetic susceptibility. Many candidate genes have been confirmed, such as the interleukin-1 gene cluster and the oestrogen alpha-receptor gene ESR1. Genome-wide linkage scans have revealed several regions harbouring novel loci, some of which are beginning to yield their genes.